Illocutionary Disagreement in the Aesthetic Realm - Zeman, Dan (Filozofia Nauki, 2022)
A recent view about disagreement (Karczewska 2021) takes it to consist in the tension arising from proposals and refusals of these proposals to impose certain commitments on the interlocutors in a conversation. This view has been proposed with the aim of solving the problem that “faultless disagreement” – a situation in which two interlocutors are intuited to be both in disagreement and not at fault – poses for contextualism about predicates of taste. In this paper, I consider whether this view applies equally well to disagreements involving aesthetic adjectives. I show, first, that it applies quite straightforwardly to predicates like “beautiful,” which presumably generate faultless disagreement. However, aesthetic adjectives like “beautiful” don’t exhaust the aesthetic sphere. A term like “balanced,” for example, while still perspectival, is said to have a more “objective” feel and usually doesn’t generate faultless disagreement: when the novice and the expert disagree on using such a term, we take it that the expert is right and the novice is wrong. I argue that Karczewska’s view has trouble explaining this difference in the profile of the two types of aesthetic predicates vis-à-vis the generation of disagreement. I also consider possible ways of coping with this problem, but I then reject them and propose a different one that is suitable for most views in the debate.